Negosiasi Spiritualitas dan Komodifikasi Agama dalam Praktik Umrah Mahasiswa Generasi Z di UIN Walisongo Semarang - Nailiya Lutfiyana Putri; Kurnia Muhajarah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the phenomenon of umrah practices among Generation Z students at UIN Walisongo Semarang within the context of growing digital culture and religious commodification. The study aims to analyze how Generation Z students spiritually interpret their umrah experience, represent it on social media, and negotiate the influence of religious commodification in their religious practices. A descriptive phenomenological qualitative approach was employed, with purposive sampling applied to ten informants who had performed umrah and actively used social media. Data were collected through semi-structured in-depth interviews, netnographic observation of informants' Instagram and TikTok accounts, and documentary study, then analyzed using the Miles and Huberman model. The findings indicate that: (1) umrah is consistently understood as a sacred act of worship that produces genuine spiritual transformation, even among digitally immersed individuals; (2) digital representations of the umrah experience are multidimensional, functioning simultaneously as personal archives, informal da'wah media, and self-presentation arenas; and (3) informants actively negotiate commodification pressures through content selection, religious narrative framing, and platform restriction. Based on these findings, this study proposes the concept of Negotiated Digital Piety as a conceptual contribution describing the active process by which Muslim Generation Z individuals balance piety, self-representation, and social media cultural pressures simultaneously.